The impact of social media influencers purchase intention in the Philippines - G. Dalangin, Jerico John; Mc Arthur, James M.B.; Salvador, Jan Benedict M.; Bismonte, Angelika B. (Faculty of Communications Science, Dr. Soetomo University, 2021)
The study aims to determine consumers' perception of the advertising efficacy of social media influencers regarding their purchase intention. The researcher believes that specific strategies and skills should be customised to attract consumers' buying intention for an influencer to be effective across social media. The study adopted the